Public Awareness of and Contact With Physicians Who Receive Industry Payments: A National Survey - Pham-Kanter, Genevieve (J Gen Intern Med, 2017)
BACKGROUND: The Physician Payments Sunshine Act, part of the Affordable Care Act, requires pharmaceutical and medical device firms to report payments they make to physicians and, through its Open Payments program, makes this information publicly available. OBJECTIVE: To establish estimates of the exposure of the American patient population to physicians who accept industry payments, to compare these population-based estimates to physician-based estimates of industry contact, and to investigate Americans’ awareness of industry payments. DESIGN: Cross-sectional survey conducted in late September and early October 2014, with data linkage of respondents’ physicians to Open Payments data. PARTICIPANTS: A total of 3542 adults drawn from a large, nationally representative household panel. MAIN MEASURES: Respondents’ contact with physicians reported in Open Payments to have received industry payments; respondents’ awareness that physicians receive payments from industry and that payment information is publicly available; respondents’ knowledge of whether their own physician received industry payments. KEY RESULTS: Among the 1987 respondents who could be matched to a specific physician, 65% saw a physician who had received an industry payment during the previous 12 months. This population-based estimate of exposure to industry contact is much higher than physician-based estimates from the same period, which indicate that 41% of physicians received an industry payment. Across the six most frequently visited specialties, patient contact with physicians who had received an industry payment ranged from 60 to 85%; the percentage of physicians with industry contact in these specialties was much lower (35–56%). Only 12% of survey respondents knew that payment information was publicly available, and only 5% knew whether their own doctor had received payments. CONCLUSIONS: Patients’ contact with physicians who receive industry payments is more prevalent than physician-based measures of industry contact would suggest. Very few Americans know whether their own doctor has received industry payments or are aware that payment information is publicly available. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-017-4012-3) contains supplementary material, which is available to authorized users.